A descriptive study of language and literacy skills of early school-aged children with unilateral and mild to moderate bilateral hearing loss. (2nd January 2020) - Nassrallah, Flora; Fitzpatrick, Elizabeth M.; Whittingham, JoAnne; Sun, Huidan; Na, Eunjung; Grandpierre, Viviane
ABSTRACT: According to population-based prevalence data, more than 40% of children diagnosed with a hearing impairment have a mild to moderate bilateral or unilateral hearing loss. Prior to newborn hearing screening, these degrees of loss were not identified until early school-age. While studies highlight the challenges of late-identified children with such a loss, little is known about the effects of early identification. This descriptive study explored the impact of mild to moderate bilateral and unilateral hearing loss on children in the early school years. Thirty-two children (aged 5–9 years) were evaluated cross-sectionally with a battery of tests to measure speech-language, phonology, and components of literacy skills. Parents also completed a questionnaire on functional auditory skills. Most outcomes were within the range of expected scores for children with typical hearing. In most cases, however, parent-reported functional auditory skills were lower than published norms. Some phonological processing skills were also below the average expected for children with typical hearing. In particular, 46.4% of children were below one standard deviation of the normative mean on the phonological memory score. Subgroup comparisons between children with unilateral ( n  = 17) and bilateral ( n  = 15) hearing loss showed no difference on all outcomes ( p  > 0.05). While scores should be interpreted with caution given the small sample size, findings reinforce the need for additional research on children with mild to moderate bilateral and unilateral hearing loss who benefit from early identification.